Surface preparation of non‐polar single‐crystalline AlN substrates. Issue 3 (22nd January 2014) - Bryan, Isaac; Akouala, Christer‐Rajiv; Tweedie, James; Bryan, Zachary; Rice, Anthony; Kirste, Ronny; Collazo, Ramón; Sitar, Zlatko
Abstract: A surface preparation technique has been developed for non‐polar m‐plane aluminum nitride (AlN) single crystalline substrates. Chemical surface treatments were conducted on chemomechanically polished m‐plane oriented AlN substrate surfaces. X‐ray photoelectron spectroscopy was used to characterize the surface chemistry after each processing step. A layer of mixed aluminum oxide‐hydroxide was identified on ambient air‐exposed surfaces. Analysis of the oxygen core level spectra showed oxygen in three bonding states, identified by the binding energies and relative separation of the fitted peaks as O 2−, OH − and H2 O. Molar ratios of different components showed the oxide to be dominantly bonded in the OH − state. Wet etching reduced the amount of surface oxides. Ammonia annealing at 1100 °C converted the aluminum oxide‐hydroxide layer to AlN. Although the overall amount of the oxide on the surface was reduced by surface treatments, the nature of the oxide remained predominantly of the OH − character. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)